2005
DOI: 10.1111/j.1365-2567.2005.02123.x
|View full text |Cite
|
Sign up to set email alerts
|

Reduced susceptibility to dextran sulphate sodium‐induced colitis in the interleukin‐2 heterozygous (IL‐2+/–) mouse

Abstract: SummaryMice homozygous for an inactivation of the interleukin-2 (IL-2) gene develop a T-cell dependent colitis. Heterozygous (IL-2 +/--) mice are clinically healthy but have been shown to express reduced levels of IL-2 in the colon. Splenocytes from the IL-2 +/--mice had a poorer proliferative response to polyclonal T-cell activation and these mice have reduced numbers of intestinal regulatory T cells (CD4 + CD25 + cells) when compared to wild type mice. When exposed to dextran sulphate sodium (DSS) IL-2 +/--m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
2
11
0
Order By: Relevance
“…Interestingly, we found enhanced CD4 ϩ cells in the lamina propia of the diseased mice, 7 days after DSS administration, which represents the acute colitis phase. Our results correlate with recent studies indicating that CD4 ϩ T cells become activated in the periphery in the DSS-induced colitis model and home to the colon during the first 3-7 days of DSS administration (55,56). Furthermore, Hall et al (43) showed that adaptive immune populations such as CD3 ϩ and B cells are also activated in the late acute phase of DSS-induced colitis.…”
Section: Figure 7 As101 Prevents the Migration Of ␣4␤7supporting
confidence: 92%
“…Interestingly, we found enhanced CD4 ϩ cells in the lamina propia of the diseased mice, 7 days after DSS administration, which represents the acute colitis phase. Our results correlate with recent studies indicating that CD4 ϩ T cells become activated in the periphery in the DSS-induced colitis model and home to the colon during the first 3-7 days of DSS administration (55,56). Furthermore, Hall et al (43) showed that adaptive immune populations such as CD3 ϩ and B cells are also activated in the late acute phase of DSS-induced colitis.…”
Section: Figure 7 As101 Prevents the Migration Of ␣4␤7supporting
confidence: 92%
“…This inWltration of M/DCs in the late phase of acute DSS induced colitis is in line with previous studies (Andres et al 2000;Sund et al 2005). However, in these reports the M/DC population was not found to be aVected as early as 1-3 days after start of DSS treatment.…”
Section: Discussionsupporting
confidence: 90%
“…9 Although the ability of DSS to induce acute colitis in mice devoid of T-cells 23,24 has led to the postulation that damage in the acute model is largely dependent on innate immunity, experiments in other strains of mice show that, even within the first 6-8 days of DSS-treatment, severity of colitis correlates positively with the presence of T cells in the large intestine. 19,25 Interestingly, our histological analyses of inflammatory infiltrates revealed a tendency of FliC-and 2H3-treated mice to accumulate more FIGURE 5. Quantification of (A) IgG1 and (B) IgG2a/b: Mice were given 2.5% DSS with their drinking water for 10 days in total; after 3 days of treatment, enemas of PBS, 1 lg FliC, or 1 lg 2H3 were given daily.…”
Section: Discussionmentioning
confidence: 91%